Effect of melatonin supplementation on biomarkers of oxidative stress and serum vitamin and mineral concentrations in heat-stressed Japanese quail - Şahin, Kazım; Onderci, M; Gursu, MF; Küçük, Ömer; Şahin, Nurhan (Poultry Science Assoc Inc, 2004)
This study was conducted to evaluate, the effects of dietary melatonin, supplementation, on biomarkers of oxidative stress, malondialdehyde (MDA) and homocysteine, and on serum concentrations of vitamin C, vitamin E, vitamin A, Fe, Zn, Cu, Cr, cholesterol, triglyceride, high-density lipoprotein cholesterol, glucose, and activities of paraoxonase (PON) and arylesterase in Japanese quail (Coturnix coturnix japonica.) exposed to high ambient temperature (34 degrees C). One hundred twenty Japanese quail (10, d old) were randomly assigned to 4 treatment groups consisting of 3 replicates of 10 birds. The birds were kept in a temperature-controlled room at 22 or 34 degrees C. Birds were fed a basal diet or the basal diet supplemented with 40 mg of melatonin/kg of diet. The experiment was terminated after 32 d. Levels of MDA in serum, liver, heart and kidney, and level of homocysteine in serum were markedly increased in heat-stressed quail, and the levels significantly decreased by melatonin supplementation (P < 0.01). Decreases in serum concentrations of vitamin C, vitamin E, vitamin A, Fe, Zn, Cu, Cr, cholesterol, triglyceride, and the activities, of PON and arylesterase induced by heat stress were partially restored by melatonin supplementation (P < 0.01). Heat stress-induced increases in serum cholesterol and glucose concentrations were also partially alleviated,by melatonin (P < 0.01). No interactions between melatonin and temperature were found on the measured parameters in the present study (P > 0.05). The results of the study indicate that melatonin supplementation attenuated the increase in oxidative stress and depletion in antioxidants caused by heat stress in Japanese quail.
Keywords: heat stress; quail; melatonin; oxidative stress; antioxidant